The Trend of TIM3 Expression on T Cells in Patients With Nontuberculous Mycobacterial Lung Disease: From Immune Cell Dysfunction to Clinical Severity - Wang, Ping-Huai; Wu, Ming-Fang; Hsu, Chi-Yu; Pan, Sheng-Wei; Shu, Chin-Chung; Cheng, Shih-Lung (Frontiers in Immunology, 2021)
Background The incidence of nontuberculous mycobacterial lung disease (NTM-LD) is increasing worldwide. Immune exhaustion has been reported in NTM-LD, but T-cell immunoglobulin and mucin domain-containing protein 3 (TIM3), a co-inhibitory receptor on T cells, has been scarcely studied. Methods Patients with NTM-LD and healthy controls were prospectively recruited from July 2014 to August 2019 at three tertiary referral centers in Taiwan. We examined TIM3 expression on the T cells from the participants using flow cytometry. TIM3 expression was analyzed for different disease statuses and after treatment. The apoptosis and cytokine profiles were analyzed according to the TIM3 expression. Results Among enrolled subjects (47 patients and 46 controls), TIM3 on CD4+ cells (6.44% vs. 4.12%, p = 0.028) and CD8+ cells (18.47% vs. 9.13%, p = 0.003) were higher in NTM-LD patients than in the controls. The TIM3 level on CD4+ and CD8+ T cells was positively associated with T-cell apoptosis in the NTM-LD patients. In stimulating peripheral blood mononuclear cells using PMA plus ionomycin, a high TIM3 level on T cells correlated with low interleukin-2 and tumor necrosis factor-alpha (TNF-α) on CD4+ cells and interferon-gamma and TNF-α on CD8+ T cells. For clinical manifestation, low body mass index (BMI), positive sputum acid-fast smear, and high radiographic score correlated with high TIM3 expression on T cells. After NTM treatment, TIM3+ decreased significantly on CD4+ and CD8+ T cells. Conclusions In patients with NTM-LD, TIM3+ expression increased over CD4+ and CD8+ T cells and correlated with cell apoptosis and specific cytokine attenuation. Clinically, TIM3+ T cells increased in patients with low BMI, high disease extent, and high bacilli burden but decreased after treatment.